Tandak Sambas (Selatasi) Elderly Exercise as An Alternative to Control Blood Pressure in Elderly Women with Hypertension - Juniartati, Erni; Fittarsih, Niya; Huda, Siti Nurul (GLOBAL HEALTH SCIENCE GROUP, 2024)
Elderly exercise helps maintain physical fitness and body freshness by training bone strength, increasing heart function, and reducing the level of free radicals in the body. The Tandak Sambas dance is a traditional dance originating from the Malay tribe in Sambas Regency, West Kalimantan, which still maintains its authenticity to this day. By combining elderly exercise and the Tandak Sambas Dance, we can create a sports program that not only helps maintain the physical health of the elderly but also preserves valuable cultural heritage. The aim of this research is to assess the Tandak Sambas Elderly Exercise (SELATASI) as a viable additional option for treating blood pressure in elderly women with hypertension in the Tekarang Community Health Center working area. This research is included in the quasi-experimental research category with sThe sample in this study was divided into 2 groups, namely the control group and the intervention group, totaling 34 respondents and each group totaling 17 respondents. The results of the Mann-Whitney test used showed a p-value of 0.06, the average systolic blood pressure in the intervention group was 122.12 mmHg after the intervention, while in the control group it was 132.88 mmHg. However, after treatment, the average diastolic blood pressure in the intervention group was 81.59 mmHg compared to 91.53 mmHg in the control group, with a p-value of 0.000. In conclusion, this research will help elderly people with hypertension to receive supportive therapy in addition to the pharmaceutical treatment they are currently undergoing.